2020
DOI: 10.1097/eja.0000000000001231
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic norepinephrine infusion or leg wrapping for postspinal hypotension in elective caesarean delivery

Abstract: BACKGROUND Because of its alpha and beta agonist properties, norepinephrine infusion is currently being studied for the prevention of spinal hypotension during caesarean delivery. Vasopressor infusions are not always possible if there is an unavailability of infusion pumps. Leg wrapping with crepe bandage is an effective technique for prevention of postspinal hypotension and could be useful in resource-poor settings. OBJECTIVE The aim of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“… 20 Because norepinephrine better maintains CO, reduces the incidence of bradycardia, and improves hemodynamic stability, it was recently put forward as an advantageous alternative to phenylephrine. 21 We found that the incidence of bradycardia was significantly lower in the norepinephrine group relative to the PE group. However, other maternal adverse events and neonatal outcomes were comparable between the two groups.…”
Section: Discussionmentioning
confidence: 61%
“… 20 Because norepinephrine better maintains CO, reduces the incidence of bradycardia, and improves hemodynamic stability, it was recently put forward as an advantageous alternative to phenylephrine. 21 We found that the incidence of bradycardia was significantly lower in the norepinephrine group relative to the PE group. However, other maternal adverse events and neonatal outcomes were comparable between the two groups.…”
Section: Discussionmentioning
confidence: 61%
“…Secondly, the recommended volume of crystalloid for a rapid infusion coload ranges between 15 and 20 ml kg −1 3 . This is in contrast to the low volume (7 ml kg −1 ) and slow infusion rate used in the present study 1 …”
mentioning
confidence: 79%
“…We applaud the authors for addressing the very pertinent issue of managing postspinal hypotension during elective caesarean delivery. 1 This randomised controlled trial reported a reduction in the incidence of spinal anaesthesia-induced hypotension using either norepinephrine infusion or leg wrapping compared to a control group. However, there are several aspects of the clinical management that make it difficult to properly understand the results.…”
Section: Editormentioning
confidence: 99%
See 2 more Smart Citations